Peran personal branding Vina Muliana dalam popularitas di tiktok - Diah Arum Titah Pujangkara; Zuhri, Saifuddin (Jurnal Komunikasi Universitas Garut: Hasil Pemikiran dan Penelitian, 2025)
Abstract This study aims to analyze the personal branding carried out by Vina Andhiani Muliana through her TikTok account @vmuliana during the period of January to June 2025. This research uses a descriptive quantitative approach with a content analysis method based on Hubert K. Rampersad’s Authentic Personal Branding framework. To ensure data validity, Krippendorff's method was applied to determine inter-coder reliability. The data was collected from 54 posts on the @vmuliana account over a six-month period, which were then analyzed based on the presence of personal branding elements such as authenticity, integrity, relevance, visibility, and message consistency. Based on thematic analysis, the TikTok account @vmuliana consistently builds a strong and relevant personal brand that aligns with the needs of the younger generation, particularly in the areas of career and personal development. Five main themes career education, self-development, personal branding, social interaction, and the use of digital media indicate that this account functions not only as an informational platform but also as a space for dialogue, motivation, and digital literacy. The content is educational, inspirational, and participatory, covering current issues such as job seeking, self-confidence, and the use of modern technologies like Artificial Intelligence, while also fostering emotional and social connection with its audience through a responsive approach. Keywords: Personal branding; tiktok; educational content; content analysis.   Abstrak Penelitian ini bertujuan untuk menganalisis personal branding yang dilakukan oleh Vina Andhiani Muliana melalui akun TikTok-nya @vmuliana dalam periode Januari hingga Juni 2025. Penelitian ini menggunakan pendekatan kuantitatif deskriptif dengan metode analisis isi berdasarkan kerangka teori Authentic Personal Branding dari Hubert K. Rampersad. Untuk menjamin validitas data, digunakan metode Krippendorff dalam menentukan reliabilitas antar-coder. Data dikumpulkan dari 54 unggahan di akun @vmuliana selama enam bulan, yang kemudian dianalisis berdasarkan kemunculan unsur-unsur personal branding seperti keautentikan, integritas, relevansi, visibilitas, dan konsistensi pesan. Berdasarkan analisis tematik, akun TikTok @vmuliana secara konsisten membangun personal branding yang kuat dan relevan dengan kebutuhan generasi muda, khususnya di bidang karier dan pengembangan diri. Lima tema utama—edukasi karier, pengembangan diri, branding pribadi, interaksi sosial, dan pemanfaatan media digital—menunjukkan bahwa akun ini tidak hanya menyampaikan informasi, tetapi juga menjadi ruang dialog, motivasi, dan literasi digital. Kontennya bersifat edukatif, inspiratif, serta partisipatif, mencakup isu aktual seperti pencarian kerja, kepercayaan diri, dan teknologi AI, sekaligus membangun kedekatan emosional dengan audiens melalui pendekatan yang responsif. Kata-kata kunci: Personal branding; tiktok; konten edukasi; analisis isi.